Etiologies and characteristics of refractory status epilepticus cases in different areas of the world: Results from a global audit. (29th August 2018) - Ferlisi, Monica; Hocker, Sara; Trinka, Eugen; Shorvon, Simon
Summary: To describe the demographics, etiologies, types of status epilepticus (SE), and outcomes in people with refractory and super‐refractory SE from around the world, we prospectively collected cases of refractory SE (RSE) treated with continuous intravenous anesthetic drugs in an intensive care unit setting through online questionnaires using "active surveillance." We collected information about 776 cases of RSE in 50 countries over 4 years. Control of SE was achieved in 74% of the cases. Neurologic outcomes were poor in 41% of patients, and 24% died. Good outcome was associated with younger age and a history of epilepsy. Etiology strongly influenced the outcome. Patients from Asia were younger, more frequently presented with convulsive SE, and were more frequently affected by infectious etiologies when compared with patients from Europe and the Americas. Despite these differences, outcomes were similar in all countries. Demographics of patients with RSE in a global audit are similar to those in prior single center series, providing evidence of generalizability of those studies. Important differences exist among patients with RSE from different regions of the world, but these do not seem to significantly influence patient outcomes.